Investigating the use of CO-oximetry for simultaneous measurement of carboxyhaemoglobin and methaemoglobin in post-mortem blood - Muleya, Jane Mahlatse (Department of Pathology, 2023)
Carbon monoxide (CO) is a gas that exerts its toxicity on humans, when inhaled, by bonding with haemoglobin (Hb) to produce carboxyhaemoglobin (COHb). This results in tissue hypoxia which can be fatal at high blood saturation levels. Carboxyhaemoglobin may be measured using a Radiometer ABL825 FLEX analyser, a spectrophotometric instrument that applies a technique called CO-oximetry to measure Hb derivatives such as COHb and methaemoglobin (MetHb). The latter is an oxidised form of Hb that can cause or contribute to mortality at high concentrations. Methaemoglobin is notorious for its instability in vitro. This study, therefore, sought to determine handling conditions best suited for the stability of MetHb in post-mortem blood such that the ABL825 FLEX analyser may be used for the simultaneous measurement of COHb and MetHb. To this end, blood samples collected from 15 cases of potential CO poisoning at Salt River Mortuary were aliquoted into red (no additive)-, green (containing lithium heparin)-, and purple (containing ethylenediaminetetraacetic acid)-top tubes. The samples were stored at 4°C or –80°C and retrieved from storage on days 0, 1, 4, 7, 14, and 30, for analysis. While COHb remained stable in all storage conditions over a 30-day period, this was not true for MetHb. When samples were stored at 4°C, a rapid increase followed by a gradual decline was observed for MetHb in all the tube types investigated. The MetHb content was at its lowest after two weeks of storage, which was consistent with COHb levels at the same time period and temperature. At –80°C, continuous increase of MetHb was observed, with the samples stored in green-top tubes showing the least amount of overall change from the reference (day zero) values. The study provided useful data regarding the stability of MetHb under the considered storage conditions, the investigators concluded that refrigerating blood samples in either red-, purple-, or green-top tube was suitable for the accurate simultaneous determination of both COHb and MetHb, if the analytes are measured immediately after collection or after two weeks of storage. Given that the nature of post-mortem forensic casework is such that suitable blood specimens are not always available for toxicological analyses, for the second aim of the study, the researchers sought to investigate the suitability of thoracic cavity fluid as an alternative specimen for the measurement of COHb. For this aim, thoracic cavity fluid collected into green-top tubes from the aforementioned cases was analysed immediately after collection. The results were compared to those obtained from the analysis of blood collected into green-top tubes and analysed on day zero (before storage). The statistical analyses used for this assessment indicated that thoracic cavity fluid would be a suitable alternative to blood for the measurement of COHb using the ABL825 FLEX analyser.